Bacteria in Agrobiology: Disease Management - Maheshwari, Dinesh K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The future of agriculture greatly depends on our ability to enhance productivity without sacrificing long-term production potential. The application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB), represents an ecologically and economically sustainable strategy. The use of these bio-resources for the enhancement of crop productivity is gaining importance worldwide. "Bacteria in Agrobiology: Disease Management" discusses various aspects of biological control and disease suppression using bacteria. Topics covered include: fluorescent pseudomonads; siderophore-producing PGPR; pseudomonas inoculants; bacillus-based biocontrol agents; bacterial control of root and tuber crop diseases; fungal pathogens of cereals; soil-borne fungal pathogens; peronosporomycete phytopathogens; and plant parasitic nematodes.
Advances in Plant Growth Promoting Rhizobacteria for Biological Control of Plant Diseases -- Bacteria for Plant Growth Promotion and Disease Management -- Bacterial Endophytes of Perennial Crops for Management of Plant Disease -- Biological Control of Pathogens and Plant Growth Promotion Potential of Fluorescent Pseudomonads -- Disease Management in Staple Crops: A Bacteriological Approach -- Beneficial Bacteria for Biological Control of Fungal Pathogens of Cereals -- Biological Control of Peronosporomycete Phytopathogens by Bacterial Antagonists -- Pseudomonas Inoculants as Agents for Plant Disease Management -- Use of Bacillus-based Biocontrol Agents for Promoting Plant Growth and Health -- Use of PGPR for Controlling Soilborne Fungal Pathogens: Assessing the Factors Influencing its Efficacy -- Plant-PGPR Interactions for Pest and Disease Resistance in Sustainable Agriculture -- Bio (Bacterial) Control of Pre- and Post- Harvest Diseases of Root and Tuber Crops -- Bacteria in the Management of Plant Parasitic Nematodes -- Rhizobacteria for Management of Fungal-Nematode Disease Complex -- PGPR-Induced Systemic Resistance (ISR) in Plant Disease Management -- Biotic Stress Management in Agricultural Crops Using Microbial Consortium -- Siderophore Producing PGPR for Crop Nutrition and Phytopathogen Suppression -- Antifungal Substances of Bacterial Origin and Management of Plant Diseases.
Keywords: Life sciences; Agriculture; Bacteriology; Plant diseases; Life Sciences; Bacteriology; Agriculture; Plant Pathology